INTERAKSI SOSIAL ANTARA SISWA REGULER DENGAN BERKEBUTUHAN KHUSUS DALAM MENINGKATKAN MOTIVASI BELAJAR (Studi Kasus di MIT Ar-Roihan Lawang – Malang) - Khusnul Isma Nuriza (EBTIDA': Jurnal Pendidikan Dasar Islam, 2023)
The Social interaction is an important and absolute thing in MIT Ar-Roihan which is an inclusive school. There are students who have difficulty in social interaction with their friends, so it influences their learning motivation. This can be seen from the action of regular students who still make "ABK" label for certain students. They have not been able to accept the conditions and support the students with special needs, so they prefer to talk and play with their regular peers. The objectives of this research are to describe and analyze the implementation process of social interaction, the factors underlying the process of social, and the implications of social interaction of regular students and students with special needs in improving learing motivation at MIT Ar-Roihan Lawang-Malang. The research approaches used are qualitative research approach, case study and study design using single case design. The data collection techniques are 1) Observation 2) Interview 3) Documentation. The results point out that: 1) The implementation process of social interaction between regular students and students with special needs in improving learning motivation are done through communication, teaching and learning process, peer groups, and extracurricular. 2) The factors underlying the social interaction are supporting factors such as social acceptance and management of schools (open house, therapy, collaboration with various parties) and inhibiting factors such as social rejection and conflict. 3) The implications are the growth of empathy, cooperation, and achievement.